Deciphering the role of NF-κB and STAT-1/3 in the pathology of a murine model of Lewy Body Dementia - Cooper, Jack John (2019)
This study was conducted to investigate and further understand the precise relationship between selected members of the transcription regulating families of both NF-kB and STAT in promoting neuroinflammation. This was attempted by measuring differences in the co-localisation of the selected proteins alongside the proliferative hypertrophy of astrocytes known as astrogliosis. Results were acquired using a previously generated ‘neuronal-specific Ubiquitin proteasome pathway (UPP) -dysfunctional mouse model of Lewy Body Dementia’. Findings show a significant increase in astrogliosis within the model. Furthermore it was observed that STAT-1 and STAT-3 have time-dependant differences in protein expression. However, definitive altered pathway regulation differences were not observed, thus a robust definition of this relationship could not be established. NF-kB could not be consistently detected suggesting an absence or unimportance in the model. This absence also hints at a potential experimental flaw, due to the ubiquitous nature of NF-kB. Ultimately, the observations recorded in this study do not present a definitive means by which the UPP dysfunction dependent inflammation of the CNS is increased by virtue of NFkB nor STAT proteins.